Studi Kualitatif tentang Pengalaman Pasien setelah Menjalani Operasi Sectio Cesarea dengan Metode ERACS di RSUD Banggai Laut, Provinsi Sulawesi Tengah - Sukmawati Sukmawati; Arlin Adam; Andi Alim (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of the Enhanced Recovery After Cesarean Surgery (ERACS) method as an innovation in the Sectio Cesarea (SC) surgical procedure aims to accelerate recovery, minimize pain, and improve patient comfort. Although it has been clinically proven, there is still limited research exploring patients' subjective experiences with this method, particularly in eastern Indonesia. This study aims to explore in depth the physical, emotional, psychological experiences, as well as perceptions of service and patient expectations after undergoing SC with the ERACS method at Banggai Laut General Hospital. The study employs a qualitative approach with a phenomenological study design. Data were collected through in-depth interviews with purposively selected informants and analyzed using Braun & Clarke's thematic analysis technique. The results showed that patients experienced rapid physical recovery, minimal pain, and were able to mobilize early. Emotionally, patients felt calm and stable, supported by good communication with medical staff and family support. However, information about the ERACS procedure before surgery was still perceived as lacking detail. Patients also hope that this method continues to be implemented with improvements in educational aspects and financial support from BPJS. Patients' experiences with the ERACS method are generally very positive and reflect the success of this approach not only clinically but also in creating a more comfortable, efficient, and humane childbirth experience. This study recommends enhancing preoperative education, postoperative monitoring, and more inclusive financial support systems.